PEMBUATAN BAKSO HERBAL DARI JAMUR TIRAM PUTIH (Pleurotus ostreatus) DAN KAYU MANIS (Cinnamomum burmannii) UNTUK MENURUNKAN KADAR KOLESTEROL - Alfarros, Daffa Farhan; Ratnasari, Dewi; Djamaluddin, Agus (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2020)
Background: Cholesterol is fat contained in the bloodstream or body cells needed for the formation of cell walls and as a raw material for several hormones. If your cholesterol is above 240 mg / dl, you have a high risk of developing diseases such as heart attack or stroke. The best prevention for lowering cholesterol is to maintain a good diet. Objective: This study aims to make stable herbal meatballs from white oyster mushroom (Pleurotus ostreatus) and cinnamon (Cinnamomum burmannii) which is empirically useful for lowering cholesterol levels.   Method: The research method used is action research using research instruments in the form of observation sheets and questionnaires. Herbal meatball preparations are made with the main ingredients of white oyster mushroom (Pleurotus ostreatus) and cinnamon (Cinnamomum burmannii) with the composition of F1 (200 grams; 0 grams), F2 (200 grams; 2.5 grams) and F2 (200 grams; 5 grams). Results: The results of the three-week organoleptic test of meatball preparations with cold storage did not show any changes in color, aroma, texture, taste and did not cause any signs of mold growth. Meanwhile, the room temperature storage only lasts for 2 days. Conclusion: The conclusion from this research is that the preferred herbal meatball preparation is the first formula and the preparation is stable in storage for 3 weeks at cold temperatures.